2013
DOI: 10.1016/j.stem.2013.03.002
|View full text |Cite
|
Sign up to set email alerts
|

A microRNA miR-34a-Regulated Bimodal Switch Targets Notch in Colon Cancer Stem Cells

Abstract: SUMMARY microRNAs regulate developmental cell fate decisions, tissue homeostasis and oncogenesis in distinct ways relative to proteins. Here, we show that the tumor suppressor microRNA miR-34a is a cell fate determinant in early stage dividing colon cancer stem cells (CCSCs). In pair-cell assays, miR34a distributes at high levels in differentiating progeny, while low levels of miR34a demarcate self renewing CCSCs. Moreover, miR34a loss of function and gain of function alters the balance between self-renewal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
335
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 331 publications
(357 citation statements)
references
References 53 publications
(67 reference statements)
18
335
1
1
Order By: Relevance
“…Indeed, recent studies show that miR-34a has a role in neural 28 and megakaryocytic differentiation 29 and is a critical cell-fate determinant in early-stage dividing colon cancer stem cells. 30 In the present study, we provide compelling evidence to support a critical role of miR-34a in SMC differentiation. It has been reported that miR-34a regulates cell cycle progress and apoptosis in cancer cells by repressing SirT1 and forming a double-positive feedback loop to regulate p53 activity.…”
Section: S Ir T 1 a C T A 2 T A G Lnsupporting
confidence: 61%
“…Indeed, recent studies show that miR-34a has a role in neural 28 and megakaryocytic differentiation 29 and is a critical cell-fate determinant in early-stage dividing colon cancer stem cells. 30 In the present study, we provide compelling evidence to support a critical role of miR-34a in SMC differentiation. It has been reported that miR-34a regulates cell cycle progress and apoptosis in cancer cells by repressing SirT1 and forming a double-positive feedback loop to regulate p53 activity.…”
Section: S Ir T 1 a C T A 2 T A G Lnsupporting
confidence: 61%
“…These aberrantly expressed miRNAs play essential roles in the regulation of TIC properties as either TIC suppressors or promoters [20][21][22][23][24] . Moreover, a series of critical signalling pathways involved in the regulation of TIC properties have been uncovered with the identification of the targets of these miRNAs 19,[25][26][27][28] . Importantly, miRNAs are also demonstrated to be promising biomarkers and amenable therapeutic targets 5,19,24 .…”
mentioning
confidence: 99%
“…Previous studies on the roles of miRNAs in regulating differentiation have indicated that they act as switches-for example, miR-489 regulating the transition from muscle stem cell quiescence to proliferation (41) or miR-34a regulating cell-fate decisions in the intestinal crypt by repressing Notch signaling (42). In cancer cell lines, we have observed that miR-215 expression can both inhibit the clonogenicity and promote the adoption of differentiated morphologies.…”
Section: Discussionmentioning
confidence: 78%